The opportunities and difficulties for M-learning to enhancing students learning results - Mnaathr, Satar Habib; Basha, Ahmed Dheyaa Basha; Alminshid, Khalid Abdulrazzaq Abdulnabi; Jamaludin, Rozinah (Enhanced Research Publications, 2013)
Under the social change that rely on technologies that create new Difficulties and challenges for universities, this paper considers the possibility of mobile learning and a subset of e-learning to influence a quantum leap in higher education, Environments universities face accelerated growth in demand for higher education, a significant reduction in government supporting and funding for education, Change in the awareness and understand of the type of knowledge, global competitiveness, changing student demographics and outlooks. At the same time unbinding mobile phones is connect a lots numbers of powerful learners to communications networks.by a review of some literature pilot on the current situation of m-learning that explores alternatives to help universities carry out its core functions of storage, processing and Launcher knowledge that can be applied to real life matters, through the study of the weakness and strengths of increased connectivity to networks of mobile communications to support Structural, self-guided interactive educational quality for learners toward using mobile devices increasingly.This article as well discusses if mobile learning can be alignment between technology development with the changing expectations of students and the implications of a variety in teaching and institutional strategies. Moreover Technologies, Consisting of mobile computing, handheld, and mobile phones, wireless and laptop, PDAs.